Inhibition of the rous sarcoma virus long terminal repeat-driven transcription by in vitro methylation: different sensitivity in permissive chicken cells versus mammalian cells - Hejnar, J; Plachý, J; Geryk, J; Machon, O; Trejbalová, K; Guntaka, R V; Svoboda, J (Virology, 1999)
Rous sarcoma virus (RSV) enhancer sequences in the long terminal repeat (LTR) have previously been shown to be sensitive to CpG methylation. We report further that the high density methylation of the RSV LTR-driven chloramphenicol acetyltransferase reporter is needed for full transcriptional inhibition in chicken embryo fibroblasts and for suppression of tumorigenicity of the RSV proviral DNA in chickens. In nonpermissive mammalian cells, however, the low density methylation is sufficient for full inhibition. The time course of inhibition differs strikingly in avian and mammalian cells: although immediately inhibited in mammalian cells, the methylated RSV LTR-driven reporter is fully inhibited with a significant delay after transfection in avian cells. Moreover, transcriptional inhibition can be overridden by transfection with a high dose of the methylated reporter plasmid in chicken cells but not in hamster cells. The LTR, v-src, LTR proviral DNA is easily capable of inducing sarcomas in chickens but not in hamsters. In contrast, Moloney murine leukemia virus LTR-driven v-src induces sarcomas in hamsters with high incidence. Therefore, the repression of integrated RSV proviruses in rodent cells is directed against the LTR.
Keywords: genetická transkripce; křečci praví; buňky 3T3; virus Moloneyho myší leukemie; Chickens; onkogenní protein pp60(v-src); Oncogene Protein pp60(v-src); Transcription, Genetic; viry ptačího sarkomu; Avian Sarcoma Viruses; Terminal Repeat Sequences; zvířata; experimentální sarkom; myši; kuřecí embryo; časové faktory; Chick Embryo; Mice; regulace exprese virových genů; buněčné linie; proviry; transfekce; DNA Methylation; kur domácí; metylace DNA; 3T3 Cells; Cell Line; DNA virů; koncové repetice; DNA, Viral; Cricetinae; Transfection; Animals; Gene Expression Regulation, Viral; Moloney murine leukemia virus; Sarcoma, Experimental; Time Factors; Proviruses